Saneamento e infraestrutura no loteamento Vila Nova em Mauriti-CE: análise de impactos ambientais e sociais - Sousa, José Bruno Furtado de (Universidade Federal Rural do Semi-Árido, 2019)
This work aims to create a sanitation proposal for the Allotment Vila Nova located on the banks of CE-384, rural area of Mauriti-CE. In the same there is a growing number of real estate construction, has no paved streets, no basic sanitation system and no electrical project. To the surroundings of this allotment there is a project of organically grown vegetables. Lack of sanitation will undermine this project and other properties. In some of these properties there are deep wells, from which water is collected for own consumption, animal and for irrigation. To solve this problem was used the knowledge of some articles, projects that work with this theme and the help of professionals in this area. It was also used of data analysis, collected in field research. This project will present an alternative to solve this problem, so as to prevent possible social and environmental impacts.
Sanitation and infrastructure in the Vila Nova subdivision in Mauriti-CE: analysis of environmental and social impacts.
MONOGRAFIA
Keywords: Loteamento; Saneamento; Impactos ambientais; Allotment; Sanitation; Environmental impacts; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA